A new protection scheme for fault detection, direction discrimination, classification, and location in transmission lines. - Jiang, J.-A (IEEE Transactions on power delivery)
This paper presents a new adaptive fault protection scheme for transmission lines using synchronized phasor measurements. The work includes fault detection, direction discrimination, classification, and location. Both fault-detection and fault-location indices are derived by using two-terminal synchronized measurements incorporated with distributed line model and modal transformation theory. The fault-detection index is composed of two complex phasors and the angle difference between the two phasors determines whether the fault is internal or external to the protected zone. The fault types can be classified by the modal fault-detection index. The proposed scheme also combines online parameter estimation to ensure protection scheme performance and achieve adaptive protection. Extensive simulation studies show that the proposed scheme provides a fast relay response and high accuracy in fault location under various system and fault conditions. The proposed method responds very well with regards to dependability, security, and sensitivity (high-resistance fault coverage).